Theological foundations for collaborative ministry - Pickard, Stephen K. (Explorations in practical, pastoral, and empirical theology., 2009)
This book examines the theological foundations of a collaborative approach to Christian ministry. The discovery that Christians are members 'one of another' creates energy and joy in ministry and empowers the Church in an age of mission. Outlining the present challenges for ministry, Stephen Pickard offers an historical perspective on ministry over the last century; develops a theory of collaborative ministry based on a dialogue between theology and science; and explores some implications of collaborative ministry for lay and ordained people of the Church. This book breaks new ground in its th.